Effects of tool shoulder size on the thermal process and material flow behaviors in ultrasonic vibration enhanced friction stir welding. (May 2020) - Shi, L.; Wu, C.S.; Fu, L.
Abstract: To improve the joint quality and lower the welding loads, ultrasonic vibration enhanced friction stir welding (UVeFSW) had been developed and had shown several benefits. The most important geometric parameter in UVeFSW tool design is the shoulder diameter, but its effect on the thermal process and plastic material flow behaviors has not been quantitatively analyzed. To elucidate these effects, an integrated computational fluid dynamics (CFD) model was adopted to quantitatively study the effects of tool shoulder diameter on the thermal process and plastic material flow behaviors in UVeFSW. It is found that UVeFSW process can have significant effects in enhancing plastic material flow and reducing the welding loads without increasing the process temperature when compared to that in FSW by using larger tool shoulder to enhance the plastic material flow. It revealed that the maximum width of the shear zone at the top surface of the workpiece was highly dependent on the shoulder diameter. However, the minimum width of the shear zone at the bottom surface of the workpiece was insensitive to the shoulder diameter. Based on the combination of the integrated CFD model with the theory of maximum traction of the tool torque on the plastic material, the optimum shoulder diameter at various welding parameters had been systematically studied. It was found that the optimum shoulder diameter decreases with an increase of the tool rotation speed, while it increases with an increase of the welding speed. This model provides a reasonable method for optimum the shoulder diameter in UVeFSW process. The integrated CFD model is validated by a comparison of the predicted and measured thermal cycles and welding loads.